Effect of oxalic acid and sulphuric acid hydrolysis on the preparation and properties of pineapple pomace derived cellulose nanofibers and nanopapers - Neenu, K. V.; Dominic, C. D. Midhun; Begum, P. M. Sabura; Parameswaranpillai, Jyotishkumar; Kanoth, Bipinbal Parambath; David, Deepthi Anna; Sajadi, S. Mohammad; Dhanyasree, P.; Ajithkumar, T. G.; Badawi, Michael (International Journal of Biological Macromolecules, 2022)
Nanocellulose is the ``green magnet'' which attracts a wide spectrum of industries towards it due to its availability, biodegradability, and possible smart applications. For the first time, pineapple pomace was being explored as an economic precursor for cellulose nanofibers. Nanofiber isolation was accomplished using a chemo-mechanical method and solution casting was adopted for the development of nanopapers. Moreover, the study examines the structural, optical, crystalline, dimensional, and thermal features of nanofibers isolated using different acid hydrolysis (oxalic acid and sulphuric acid) methods. Fourier-transform infra-red spectroscopy, 13C solid-state nuclear magnetic resonance spectroscopy, and X-ray diffraction analysis indicated the presence of type I cellulose. The transmittance, crystallinity index, and thermal stability of PPNFS (sulphuric acid treated fiber) were greater than PPNFO (oxalic acid treated fiber). The transmission electron microscopy and dynamic light scattering analysis confirmed the nanodimension of PPNFO and PPNFS. While comparing the optical and mechanical properties of nanopapers, PPNFS outperforms PPNFO. The tensile strength of the prepared nanopapers (64 MPa (PPNFO) and 68 MPa (PPNFS)) was found to be high compared to similar works reported in the literature. The prepared nanopaper is proposed to be used for food packaging applications.
Keywords: cellulose nanofibers; Cellulosic nanopapers; Pineapple pomace

Extraction, characterization, and life cycle assessment of nanosilica from millet husk: sustainable alternative with low environmental impact - Dominic, C. D. Midhun; Rosa, Derval dos Santos; Barbosa, Rennan Felix da Silva; Anagha, O. V.; Neenu, K. V.; Begum, P. M. Sabura; Kumar, V. Aswathy; Parameswaranpillai, Jyotishkumar; Siriwong, Chomsri; Ajithkumar, T. G.; Shelke, Ankita; Pasc, Andreea (Journal of Cleaner Production, 2024)
Eco-friendly approaches for silica production are highly researched to respond increasing industrial demand for bio-nanofillers. Herein, nanosilica of 10-20 nm with mesoporosity was obtained through a mild oxalic acid pre-treatment of millet husk, followed by calcination at 700 degrees C for 2 h. Compared with commercial precipitated silica (CS) and millet husk ash (MHA) directly obtained by calcination of the husk, the pre-treated silica (MHS) had higher purity, revealed using EDX spectroscopy. Moreover, FTIR and Si-29 NMR showed a higher condensation degree in MHS with 73% of Q4 siloxane bonds vs 4% in MHA. The release of the metal and organic impurities from the husk also allows to reduce the crystallinity of MHS, and to increase the specific surface area from 82 m(2)/g in MHA to 238 m(2)/g in MHS. The type II N-2 adsorption-desorption isotherms of MHA and MHS indicate aggregates of non-porous silica particles. MHS also demonstrated remarkable thermal resilience. According to the LCA analysis, MHS has a 40% lower impact on global warming, a 38% lower impact on human carcinogenic toxicity, and a 38% lower impact on terrestrial acidification compared to rice husk nanosilica. This research thus addresses sustainability challenges by repurposing millet husks, which are readily available due to continuous millet cultivation, particularly in India. By reducing the ecological impact of husk disposal through burning, this study offers an economically viable technology for high-purity silica production, aligning with global efforts to combat climate change and promote sustainable practices.
Keywords: Life cycle assessment; Millet husk; Nanosilica; Oxalic acid

Extraction of highly crystalline and thermally stable cellulose nanofiber from Heliconia psittacorum L.f. leaves - Paul, Sharon; Joseph, Anto; Hridhya, P. D.; Badawi, Michael; Ajithkumar, T. G.; Parameswaranpillai, Jyotishkumar; Asrofi, Mochamad; Dominic, C. D. Midhun (International Journal of Biological Macromolecules, 2025)
Extracting cellulose nanofibers (CNF) from agro-waste is one of the promising and practical ways to develop sustainable nanocomposites. In this study, cellulose nanofibers were extracted from the leaves of Heliconia psittacorum for the first time. The combination of oxalic acid hydrolysis (5 wt%) and steam explosion was used for the isolation of CNF from the leaves of Heliconia psittacorum. The structural and chemical features of the prepared CNF were analyzed using various techniques, including Fourier Transform Infrared Spectroscopy (FTIR), Solid state 13C Nuclear Magnetic Resonance Spectroscopy (13C NMR), Scanning Electron Microscopy (SEM), Energy Dispersive X ray analysis (EDX), Transmission electron Microscopy (TEM), X-Ray Diffraction (XRD) and Thermogravimetric analysis (TGA). TEM micrographs reported 15 to 40 nm diameter for the nanofibers synthesized. XRD analysis reported 91 % crystallinity index for CNF, whereas that of the untreated sample was 76 %. The maximum degradation of the CNF is reported at 355 degrees C, exceeds the untreated sample (316 degrees C). The tensile strength of the CNF derived paper was found to be 23 MPa. The recovered nanocellulose can be further utilized for various applications such as the automobile industry for developing lightweight parts, biosensors, super capacitors, absorption of greenhouse gases, wastewater treatment, and packaging applications.
Keywords: biomass valorization; Nanocellulose; Waste to resource